No association of G‐protein‐coupled receptor kinase 5 or β‐adrenergic receptor polymorphisms with Takotsubo cardiomyopathy in a large Australian cohort. (July 2013) - Figtree, Gemma A.; Bagnall, Richard D.; Abdulla, Irfan; Buchholz, Stefan; Galougahi, Keyvan Karimi; Yan, Warren; Tan, Timothy; Neil, Chris; Horowitz, John D.; Semsarian, Chris; Ward, Michael R.
<x xml:space="preserve">Abstract</x> Aims Takotsubo cardiomyopathy (TC) is an increasingly recognized syndrome in which patients present with chest pain and ST changes, and are observed to have reversible LV apical ballooning in the absence of angiographically significant coronary artery stenosis. Although the pathophysiology remains unclear, the syndrome occurs almost exclusively in women, and is often triggered by stress. Recent small studies have reported association of TC with functional variants in the G‐protein‐coupled receptor kinase 5 (GRK5) gene, as well as in the β1‐adrenergic receptor (β1AR) and β2AR. Methods and results We tested these associations in a larger cohort of 92 TC patients. In addition we examined for the association of polymorphisms in the oestrogen receptor α (ERα) and catechol‐O‐methyl transferase (COMT) with the occurrence of TC, by comparing the allele frequency of these variants in the TC cohort with that in previously genotyped large Caucasian cohorts. Ninety‐two patients with TC were recruited from four Australian centres; they had an age range of 41–90 years (mean ± SD = 66.3 ± 9) and 89/92 were female. There were no significant differences in allelic frequency in the TC group vs. the historic control database for any of the loci. Conclusion In the largest genotyped TC cohort in the literature, we have found no association of genetic variants in the ERα, β1AR, β2AR, or COMT genes, or with the previously implicated GRK5, with occurrence of the syndrome.